AN ANALYSIS OF STEPHENIE MEYER’S TWILIGHT NOVELS AS MODERN LITERARY FAIRY-TALES - Ergasheva Nilufar Baxodir qizi (PEDAGOGS, 2024)
The article presents an analysis of Stephenie Meyer’s Twilight novels as modern literary fairy-tales. To this end, the discussion will refer to structuralist critics, and identify “narrative functions” from folktales (stock images and episodes, stock character functions, characteristic sequences of episodes), used by Meyer in her vampire novels. As it turns out, Meyer modified folklore material to sustain a long and variously themed narrative: by embedding numerous subplots, by rearranging functions between characters, and creating composite and collective characters that combine contradictory functions. The author transformed several folktales into a series of four novels about coming of age in the twenty-first-century United States. A detailed analysis of Meyer’s modifications of the folktale partially corroborates the feminist critique of Meyer’s representation of the protagonists as reinforced versions of cultural stereotypes and gender roles. However, some transformations, especially Meyer’s assignment of the hero-function to the female protagonist Bella, seem to suggest just the opposite, thus leading to the conclusion that the Twilight novels reflect the confusion caused by contradictory role-models and aspirations, the confusion that seems to be inherent in a coming-of-age novel.